Investigating the four-level inquiry continuum on college students' higher order thinking and peer interaction tendencies. (27th September 2021) - Lu, Kaili; Yang, Harrison; Xue, Hui
Research positively associates inquiry-based learning (IBL) activities to the benefits of students' higher order thinking, collaboration, and communication skill. However, few studies have examined the impact of IBL activities on higher order thinking skills (HOTS) and peer interaction at all levels of inquiry. This study examined 58 college students' perceptions of their HOTS and peer interaction tendencies from the perspective of a four-level inquiry continuum process. Overall, the study found that as IBL activities moved from the first level of inquiry (confirmation inquiry) to the fourth level of inquiry (open inquiry), students' HOTS and peer interaction tendencies strengthened. Further analysis showed that students' HOTS and peer interaction tendencies changed significantly at different levels of IBL activities. Highly student-centred IBL activities were significantly more effective than highly teacher-directed activities. In addition, there was a strong correlation between students' HOTS and peer interaction tendencies in IBL activities. The findings of this study have practical implications for educators, indicating that they should design, develop, and implement IBL activities, considering all four levels of inquiry as a continuum. Educators should also find ways to leverage the relationship between students' higher HOTS and peer interaction.